The Impact of the Mobile Legends Games on the Psychosocial Health of Children - Fadhil Nur Hidayat; Aminul Qodat (Jurnal Ilmu Pendidikan Dasar Indonesia, 2024)
This study aims to identify the impact of the Mobile Legends Game on the psychosocial aspects of children. This study conducted interviews, observations, and documentation on children aged 10-12 years who actively play this game and their parents. This study was conducted for two months in the Gowok housing area, Sleman, Yogyakarta. The data collected were analyzed using the Miles and Huberman method. The results of the study indicate that active participation in the Mobile Legends Game impacts children's psychosocial aspects. Social acceptance and the surrounding environment in this game influence children's identity. The rules in the game can limit the exploration of children's identity and freedom. In conclusion, active participation in the Mobile Legends game impacts children's psychosocial aspects. These findings provide further understanding of the impact of this game on children, pragmatic mindsets, and internal and external factors that influence children's psychosocial elements.